The confidential papers of Fernando VII: identification, analysis and proposal for standardized description - Rodríguez Castillo, Miguel (Revista General de Información y Documentación, 2013)
Using the archivist methodology of investigation it is established the chain of custody of the hundred and eight binded volumes that form this document series and it is analyzed and briefly described the content of them, discovering this way the subjects of interest for Fernando VII. It’s also proposed a normalized description of these documents according to international standard ISAD (G)